PERANCANGAN ANIMASI 2D MENGENAI MENSTRUASI UNTUK REMAJA PUTRI DENGAN METODE MDLC: 2D Animation Design About Menstruation For Adolescent Girl Using the MDLC Method - Bayu Syahputra; Deli Deli; Christine Gabriella (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2024)
Puberty in teenage girls is usually marked by menarche or first menstruation. Menstruation is a process of shedding of the lining of the uterine wall. There are several factors that cause abnormal menstrual cycles such as stress, nutritional problems, hormonal disorders and also chronic diseases. Personal hygiene during menstruation is also important for women. If a woman's personal hygiene is not maintained properly, it is likely that infections will occur in the reproductive organs. Most young women feel embarrassed to consult a doctor if they experience complaints regarding the health of their reproductive organs and reproductive organ problems. By designing a 2D animated video about menstruation, the aim is to provide information and insight to young women. The method that will be used for data collection is by interviewing experts in the field and the method used in designing 2D animated videos is the MDLC (Multimedia Development Life Cycle) method which includes several stages, namely concept, design, data collection, creation, testing, and distribution. Then the final results of the animated video will be tested with experts in the field of female reproductive organs. In designing 2D animation, you will use the applications Adobe Illustrator, Adobe Audition, Adobe Animate, and Adobe After Effects. The result of this research is a 2D animated video entitled "What is Menstruation?" as a medium of information and insight.